2005
DOI: 10.1100/tsw.2005.78
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory, Antinociceptive, and Gastric Effects ofHypericum perforatumin Rats

Abstract: The pharmacological activity of Hypericum perforatum was assessed using models of inflammation, nociception, and gastric mucosal injury in rats. H. perforatum was given systemically as well as orally. When administered systemically, H. perforatum (50–300 mg/kg, s.c.) produced a dose-related and significant inhibition of the edematogenic response to s.p. injection of carrageenan. The percentages of maximal inhibition by the above doses were 53.7, 61.3, and 75.3%, respectively (compared to 90% after 50 mg/kg flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The present study showed that DES (50 mg·kg −1 ) inhibited much lower (about 20%) the CG‐induced paw edema compared with the same dose of fluoxetine (another type of antidepressant); its edematous response to CG injection is about 90% . These antidepressants also show a different effectiveness in another experimental model—septic shock; given preventively, the drugs markedly decrease the circulating levels of TNF‐ α (a cytokine involved in systemic inflammation) and mortality (50% mortality in fluoxetine‐treated group and 30% in DES‐treated groups).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The present study showed that DES (50 mg·kg −1 ) inhibited much lower (about 20%) the CG‐induced paw edema compared with the same dose of fluoxetine (another type of antidepressant); its edematous response to CG injection is about 90% . These antidepressants also show a different effectiveness in another experimental model—septic shock; given preventively, the drugs markedly decrease the circulating levels of TNF‐ α (a cytokine involved in systemic inflammation) and mortality (50% mortality in fluoxetine‐treated group and 30% in DES‐treated groups).…”
Section: Discussionmentioning
confidence: 56%
“…confirm the above findings. The authors establish a significant reduction of paw edema by imipramine, amitriptyline and clomipramine and about 90% decrease by 50 mg·kg −1 of fluoxetine in the edematogenic response to CG injection . The partially suppressed fluoxetine anti‐edema effect by the opioid antagonist naloxone suggests that both serotonergic and opioid systems are likely involved in the modulating action of fluoxetine on peripheral inflammation .…”
Section: Introductionmentioning
confidence: 86%
“…Analgesic activity was tested in mice using the hot plate according to a previously reported method [Abdel‐Salam, ] with slight modifications. Forty Swiss mice were divided into 5 groups ( n = 8 per group).…”
Section: Methodsmentioning
confidence: 99%
“…Analgesic activity was tested in mice using the hot plate according to (Abdel-Salam 2005) with slight modifications. Forty Swiss mice were divided into five groups (n = 8).…”
Section: Hot Plate Testmentioning
confidence: 99%